Peranan Pemimpin Gereja Bagi Jemaat Dalam Menjaga Keutuhan NKRI Dari Ancaman Radikalisme - Harita, Novi Saria; Setiawan, David Eko (IAKN TORAJA, 2022)
Abstract: Radicalism is an understanding or practice of a doctrine that is considered true and is also an extreme idea. This kind of understanding can be a threat to the sustainability of the nation, religion, ethnicity and race in Indonesia. This understanding arises because the values ​​of Pancasila are no longer implemented in the life of the nation and state. So what is the role of church leaders in maintaining the integrity of the Republic of Indonesia from the threat of radicalism in the lives of their congregations? To answer these questions, in this study the author uses a descriptive qualitative approach with the library method. The purpose of this study is to explain the role of a church leader in maintaining the integrity of the Unitary State of the Republic of Indonesia from the threat of radicalism to the congregation he leads. The results of this study are church leaders must provide guidance to local church members, encourage congregations to care for each other through deacon services and encourage congregations to be involved in the nationalism movement. Abstrak: Radikalisme adalah paham atau pengamalan suatu doktrin yang dianggap benar dan juga merupakan gagasan yang ekstrim. Pemahaman seperti ini dapat menjadi ancaman bagi keberlangsungan bangsa, agama, suku dan ras di Indonesia. Pemahaman ini muncul karena nilai-nilai Pancasila tidak lagi diimplementasikan dalam kehidupan berbangsa dan bernegara. Lantas bagaimana peran pimpinan gereja dalam menjaga keutuhan NKRI dari ancaman radikalisme dalam kehidupan jemaatnya? Untuk menjawab pertanyaan tersebut, dalam penelitian ini penulis menggunakan metode kepustakaan. Tujuan dari penelitian ini adalah untuk menjelaskan peran seorang pemimpin gereja dalam menjaga keutuhan Negara Kesatuan Republik Indonesia dari ancaman radikalisme kepada jemaat yang dipimpinnya. Hasil dari penelitian ini adalah pemimpin gereja harus melakukan pembinaan terhadap warga gereja lokal, mendorong jemaat untuk saling peduli melalui pelayanan diakonia dan mendorong jemaat untuk terlibat dalam pergerakan nasionalisme.